Axial and Lateral Quasi-Static Crushing Behaviour of Segmented and Non-Segmented Composite Tubes - Abosbaia, Al-Hadi A. Salem (2003)
Considerable research interest has been directed towards the use of composite for crashworthiness applications, because they can be designed to provide impact energy absorption capabilities which are superior to those of metals when compared on weight basis. The use of composite circular tubes i n structural applications IS becoming more widespread throughout the auto motives, aircraft industry. This work examines the effect of segmentation on the crushing behaviour, energy absorption and failure mode of composite circular tubes. The segmented composite tube consists of more than one material, each with its own specific functions. Through out this study, segmented and non segmented composite tubes with different sequences were experimentally investigated under axial and lateral loading conditions. The effect of fibre reinforcement type and segments sequence on energy absorption and load carrying capacity were also presented and discussed. Load-displacement curves and deformation histories of typical specimens are presented and discussed. The results showed that non-segmented composite tubes were found to be very brittle (i.e. tissue mat glass fibre/epoxy tubes), and show very low initial failure crush load value of 1 .8 9kN, as well as low specific energy absorption value of O.065kJ/kg under axial crushing. Whereas, the carbon fabric fibre reinforced plastic (CFRP) tubes showed highest load-carrying capacity among the tested specimens with initial fai lure crush load value of I8.85kN as well as specific energy absorption value of I9 .27kJ/kg. On the other hand, segmented composite tubes including the tissue mat glass fibres were found to suffer from low energy absorption and the catastrophic failure mechanism initiated at the part made of tissue mat glass fibre/epoxy. Segmented Composite tubes from carbon fabric fibre and cotton fabric fibres exhibited good specific energy absorption value of 13.53 kj/kg as well as stable load-carrying capacity under axial loading. A change in segmentation sequence affects the crush loads significantly just for double fibre segmented composite tubes under lateral loading. The axial loaded segmented composite tubes have better load carrying capacity and energy absorption capability compared to the laterally loaded segmented composite tubes, and the failure modes were quite different.